Мова як елемент культури і чинник державотворення - Іванюк, О. А. (ХНУРЕ, 2020)
Language is the property of mankind. It is not only the most powerful means of communication, a tool of thought, but also a necessary condition for the existence of the people. Language is aimed at the inner world of man, his psyche, and the outer world of nature and human relationships.
Keywords: українська державність; українознавство